2015
DOI: 10.1515/johh-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the rheological behaviour of coal ash slurries

Abstract: Extensive experimental investigations were carried out to evaluate the rheological behaviour of fly ash (FA) slurry without and with the addition of bottom ash (BA) and BA slurry without and with the addition of FA. The FA slurries exhibited Bingham behaviour at solid mass concentrations ranging from 60-65% and mixing proportions from 10-40%. A substantial reduction in yield stress was observed except for mixing proportion of 40% on which the yield stress and viscosity were increased drastically for all solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…Pani et al [18] studied the rheological behaviour of coal ash slurry and investigated the effects of chosen additives on it. Assefa and Kaushal [19] carried the experimental investigations on bottom/fly-ash slurry with/without additions of fly/bottom ash in order to evaluate its rheological behaviour. The extensive drop in the yield stress and the viscosity is observed with 30% mixing proportions to the fly ash slurry whereas the aforesaid parameters rapidly shoot up with 40% of mixing proportions at all solid concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Pani et al [18] studied the rheological behaviour of coal ash slurry and investigated the effects of chosen additives on it. Assefa and Kaushal [19] carried the experimental investigations on bottom/fly-ash slurry with/without additions of fly/bottom ash in order to evaluate its rheological behaviour. The extensive drop in the yield stress and the viscosity is observed with 30% mixing proportions to the fly ash slurry whereas the aforesaid parameters rapidly shoot up with 40% of mixing proportions at all solid concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The flow behavior of fly ash slurry depends on different factors, for instance, shape of particles, particle size distribution, solid concentration in slurry, and slurry viscosity. 9 Viscosity and shear stress of slurry could be decreased by adding different additives, thereby enhancing the possibilities of a high percentage of solids in the slurry transportation. 10 Many investigators have examined the effects of various additives on the rheological behavior of fly ash slurry at high concentrations during pipeline transportation.…”
Section: Introductionmentioning
confidence: 99%
“…The flow behavior of the slurry in long distance pipeline is also influenced by pipeline design parameters such as diameter of pipe and pipe bends and these parameters can be optimized by using CFD modeling in FLUENT software (Kaushal and Tomita, 2002; Kaushal et al , 2005; Kaushal et al , 2012, 2013; Kumar et al , 2015). It was experimentally observed that fly ash samples at higher concentrations with finer particles also affect the viscosity of the sample (Assefa and Kaushal, 2015; Singh et al , 2015, 2016). Chemical additives also affect the rheological and flow properties of slurry.…”
Section: Literature Reviewmentioning
confidence: 99%